DAULAH UMAYYAH EKSPANSI DAN SISTEM PEMERINTAHAN MONARCHIHERIDETIS - Henny Yusalia (Wardah, 2012)
Umayyads with Muawiyah leader, no doubt is one of the major figures in the history of Islam. One of the greatest achievements is the ability to expand the areas embraced Islam. Therefore, renowned Muawiyah with the power of expansion, so that Islam may spread to many other countries and regions quickly. Of course it's spread, often using armed force. On the other hand, what the Umayyads, is against the spirit and the things that have been done in the era of the Prophet and the first four caliphs. In particular the system of government and other areas pengislaman patterns. Unity and pluralism are valued at the time of Rasullullah SAW it was revived by the Arabization of the Umayyads. This paper is not research, but the results of the literature review the authors. In essence to describe the phenomenon of Bani Umayya.